Anticipating climate change impacts on Mongolian salmonids: bioenergetics models for lenok and Baikal grayling. Issue 3 (2nd April 2016) - Hartman, Kyle J.; Jensen, Olaf P.
Abstract: The Eg–Uur River ecosystem in north‐central Mongolia provides an opportunity to study salmonid species in a system that has already experienced significant climate change. These species are currently imperilled in Mongolian waters, with Baikal grayling ( Thymallus arcticus baicalensis) listed as near‐threatened and lenok ( Brachymystax lenok ) listed as vulnerable on the Mongolian red list. Air temperature records demonstrate that in the last 40 years Northern Mongolia's rate of warming has been three times greater than the northern hemisphere average. Despite alarming trends in air temperatures, little is known of the thermal ecology of these species. Due to the threat of climate change to these species, the objective of our study was to quantify metabolic costs for these species from streamside routine metabolic measures and derive bioenergetics models that we used to assess potential climate change response. Streamside measurements of metabolism were remarkably consistent with expectations from measures of other salmonids gathered under more closely controlled laboratory conditions. Metabolism increased exponentially with temperature for both species. The resulting preliminary bioenergetics models suggest these species are already experiencing temperatures near their upper levels for growth during summer and conditions are expected to deteriorate with warming. Even a modest 2 °C increase in water temperatures during ice out would result in a 59% reduction in growth of lenok, and an inability of Baikal grayling to grow (if food levels remained unchanged) or a 14–23% increase in consumption in order to maintain current growth rates.